Tindak Pidana Pembobolan Rekening Via Online Berkedok Link (Suatu Kajian terhadap Perundang-Undangan Informasi dan Transaksi Elektronik) - Sahabuddin, S.; Andrizki, Laras Dwi (Universitas Batanghari Jambi, 2024)
Along with the development of technology, the use of which is increasingly massive in society, especially the use of online systems in financial traffic through electronic transactions, has given rise to evil intentions from people who have expertise in the field of information and electronics. One of them is hacking online accounts by hackers using fraudulent mode under the guise of a link sent via short message to the target and if the link is accepted and opened by the target, the hacker will easily carry out the action of draining the account. Viewed from a normative aspect, the Republic of Indonesia has actually provided protection to the public by passing various laws, for example in the scope of information and electronic transactions through Law Number 19 of 2016, an amendment to Law Number 11 of 2008 concerning information and electronic transactions. which threatens anyone who has committed a criminal act of breaking into another person's account via an electronic system with imprisonment, but this threat is not enough to provide a deterrent to the perpetrators, even though on the other hand the victims of this crime experience quite large losses and cause anxiety in society which is quite high in the security of their accounts. So this is quite interesting to research, especially from the normative aspect of the legislation. This research uses a normative type of research with a legal approach, with this research it is hoped that it can provide a clear picture of the criminal sanctions threatened by perpetrators of online account hacking under the guise of links, and it is also hoped that it will further provide an understanding of the importance of legal protection. against the account holders of the actions of the perpetrators of this crime.